Research on Bank Hall Service Management Strategy of Rural Commercial Bank - Shang, Jianhong (Pacific International Journal, 2024)
With the transformation and upgrading of financial technology, people's demand for personalized banking services is getting higher and higher. In order to meet people's growing financial needs, commercial banks have carried out a series of branch transformation and upgrading. As the main business place of physical network, the hall of rural commercial bank plays an irreplaceable role in electronic channels and virtual places. After decades of development, rural commercial banks have carried out a series of reforms and innovations. At present, the external layout of hall outlets, such as intelligent machinery, electronic equipment, and standardized network construction, has achieved initial results. Under the background of network transformation, the network construction of rural commercial banks has undergone great changes, but the concept of hall operation service has not matched the network construction in time, and can not adapt to the requirements of banking development under the new situation. In view of this situation, this paper explores the hall management and operation services of rural commercial banks, with the purpose of improving the hall service efficiency of rural commercial banks, improving the enthusiasm of employees, improving the service quality and efficiency, and increasing the profitability of banks.Taking the branch hall management of commercial banks in rural areas as the entry point, this paper uses literature research, process reengineering, salary management and other relevant theoretical research methods, SWOT analysis and other methods to analyze the problems existing in the transformation and upgrading process of branch halls of rural commercial banks, such as unreasonable staffing, cumbersome processes, low efficiency and low customer satisfaction. This paper explores the causes of such problems according to the problems, that is, backward management system, market positioning, low entry conditions for competitors, and low scale effect. Finally, it aims to improve system management, optimize organizational framework, integrate hall zoning, refine the division of labor, increase scientific and technological support, and innovate service modes. Improve the assessment mechanism, and put forward constructive suggestions on hall management and marketing strategy in the process of network transformation and upgrading to employees. The research in this paper can improve the service quality and efficiency of hall staff, improve the post adaptability of hall staff, thus improve marketing performance, realize the transformation and upgrading of outlets, and achieve greater economic benefits of rural commercial banks.